ICC 2019 - 2019 IEEE International Conference on Communications (ICC) 2019
DOI: 10.1109/icc.2019.8761605
|View full text |Cite
|
Sign up to set email alerts
|

Low Complexity Iterative Detection for a Large-Scale Distributed MIMO Prototyping System

Abstract: In this paper, we study the low-complexity iterative soft-input soft-output (SISO) detection algorithm in a large-scale distributed multiple-input multiple-output (MIMO) system. The uplink interference suppression matrix is designed to decompose the received multi-user signal into independent single-user receptions. An improved minimum-mean-square-error iterative soft decision interference cancellation (MMSE-ISDIC) based on eigenvalue decomposition (EVD-MMSE-ISDIC) is proposed to perform low-complexity detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…A pioneering work [20] has investigated the asynchronous reception effects caused by DSDs on distributed massive MIMO-OFDM systems at microwave frequencies. The same effect has been observed in a distributed MIMO prototyping system [21]. However, to our knowledge, the impact of DSDs on mmWave DASs with hybrid structures has not been investigated.…”
Section: Introductionsupporting
confidence: 70%
“…A pioneering work [20] has investigated the asynchronous reception effects caused by DSDs on distributed massive MIMO-OFDM systems at microwave frequencies. The same effect has been observed in a distributed MIMO prototyping system [21]. However, to our knowledge, the impact of DSDs on mmWave DASs with hybrid structures has not been investigated.…”
Section: Introductionsupporting
confidence: 70%
“…CF massive MIMO has been shown to achieve higher spectral efficiency than centralized massive MIMO and small cell [117]. Our recent prototyping system in largescale distributed MIMO has demonstrated that the data rate of 10 Gbps could be achieved by a 128×128 large-scale distributed MIMO (or CF massive MIMO) with 100 MHz bandwidth [118]. However, CF massive MIMO is also facing some obstacles such as high implementation complexity, high requirement of backhaul/fronthaul, and difficulty in synchronization and channel state information (CSI) acquisition.…”
Section: Cf Massive Mimomentioning
confidence: 99%
“…However, this optimization is a non-convex problem which causes a high computational complexity. In [130], a low-complexity iterative soft-input soft-output (SISO) detection algorithm in a distributed large-scale MIMO system based on an improved MMSE iterative soft decision interference cancellation is proposed and experimentally tested. The prototype system has shown that a data rate of 10 Gbps could be achieved by a 128×128 cell-free massive MIMO with 100 MHz bandwidth.…”
Section: B Detection In Cell-free Massive Mimomentioning
confidence: 99%